1983
DOI: 10.1063/1.446255
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic twist properties of some nematic liquid crystalline azoxybenzenes

Abstract: The static and dynamic behavior of the Frederiks transition for twist of a uniform planar nematic sample in an external magnetic field has been studied by monitoring the associated conoscopic figure. In particular, the decay of this figure after the field has been switched off is considered in detail in order to obtain results for the twist viscosity γ1. Results for the twist elastic constant K2 and for the viscosity γ1 are reported for the homologous series of p, p′-dialkylazoxybenzenes. K2 is found to be sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…It has been demonstrated that the elastic constants depend on molecular structure, intermolecular association, and temperature of nematics [271,274,275]. The ratio K 33 =K 11 was found to be less than unit for a weakly polar two-ring thioester derivative [276], which is similar in value to those of other weakly polar derivatives [3].…”
Section: Viscoelastic Propertiesmentioning
confidence: 77%
“…It has been demonstrated that the elastic constants depend on molecular structure, intermolecular association, and temperature of nematics [271,274,275]. The ratio K 33 =K 11 was found to be less than unit for a weakly polar two-ring thioester derivative [276], which is similar in value to those of other weakly polar derivatives [3].…”
Section: Viscoelastic Propertiesmentioning
confidence: 77%
“…It has been shown that the elastic constants depend on molecular structure, intermolecular association, and temperature of NLCs [276][277][278]. The elastic constant ratio K 33 =K 11 of liquid crystals is an important parameter for supertwisted nematic liquid crystal displays (STNLCDs), defining their electro-optical performance [279].…”
Section: Visco-elastic Propertiesmentioning
confidence: 99%
“…It has been shown that the elastic constants depend on molecular structure, intermolecular association, and temperature of nematic LCs [169][170][171]. The elastic constant ratio K 33 =K 11 of liquid crystals is an important parameter for supertwisted nematic liquidcrystal displays (STN-LCDs) and define their electrooptical performance [172].…”
Section: Viscoelastic Propertiesmentioning
confidence: 99%